Source Analysis of Triphasic Waves Using Quantitative Neuroimaging - Meira, Alex Tiburtino [UNESP]; Alves, Karen Fernanda; Rezende, Thais O P; Schelp, Arthur Oscar; Betting, Luiz Eduardo (Wolters Kluwer, 2022)
PURPOSE: Triphasic waves (TWs), a common EEG pattern, are considered a subtype of generalized periodic discharges. Most patients with TWs present with an altered level of consciousness, and the TW pattern is believed to represent thalamocortical dysfunction. However, the exact meaning and mechanism of TWs remain unclear. The objective of the current study was to evaluate the source of TWs using EEG source imaging and computerized tomography. METHODS: Twenty-eight patients with TWs were investigated. Source analysis was performed on the averaged TWs for each individual, and source maps were extracted. Normalization and automatic segmentation of gray matter were performed on computerized tomography scans before analysis. Finally, voxelwise correlation analyses were conducted between EEG source maps and gray matter volumes. RESULTS: Source analyses showed that the anterior cingulate cortex was mainly involved in TWs (16/28 patients, 57%). Correlation analyses showed moderate positive and negative correlations between source location and gray matter volumes for the posterior cingulate ( T = 2.85; volume = 6,533 mm 3 ; r = 0.53; P = 0.002) and the superior frontal gyrus ( T = 2.54; volume = 18,167 mm 3 ; r = -0.48; P < 0.0001), respectively. CONCLUSIONS: The results suggest that the anterior cingulate is involved in the origin of TWs. Furthermore, the volumes of posterior brain regions were positively correlated with TWs, indicating a possible preservation of these structures. Conversely, the volumes of anterior regions were negatively correlated with TWs. These findings may indicate a structural pattern necessary for the generation of the abnormal network responsible for TWs.